A novel cylindrical profile measurement model and errors separation method applied to stepped shafts precision model engineering. (January 2022) - Liu, Yongmeng; Mei, Yingjie; Sun, Chuanzhi; Li, Ruirui; Wang, Xiaoming; Wang, Hongye; Tan, Jiubin; Lu, Qing
Highlights: Aiming at the model engineering of large-scale stepped shafts and improving the surface profile measurement accuracy of large-scale stepped shafts, a cylindrical profile measurement model containing seven systematic errors is designed. Further, a multi-systematic errors separation method is proposed based on the seven-systematic errors in the cylindrical profile measurement model. First, the autocollimator and image pro-cessing are used to accurately extract the verification parameters, and then the stepwise estimation method and the equalisation optimizer (EO) are used to obtain the sectional and spatial parameters. The measurement experiment is based on the large-scale stepped shaft profile measurement device, and uses the coaxiality indicator to evaluate the pro-file measurement accuracy of the large-scale stepped shaft, and compares our model with the dual-systematic errors model and the five-systematic errors model. Abstract: A large-scale stepped shaft is an important component in precision machinery manufacturing. Aiming at the model engineering of large-scale stepped shafts and improving the surface profile measurement accuracy of large-scale stepped shafts, a cylindrical profile measurement model containing seven systematic errors is designed, in which the eccentricity error, tilt error, sensor probe radius error, probe offset error, probe support rod tilt error, and horizontal and vertical rail tilt error are considered. Further, a multi-systematic errors separation method is proposed based on the seven-systematic errors in the cylindrical profile measurement model. First, the autocollimator and image processing are used to accurately extract the verification parameters, and then the stepwise estimation method and the equalisation optimizer (EO) are used to obtain the sectional and spatial parameters. The measurement experiment is based on the large-scale stepped shaft profile measurement device, and uses the coaxiality indicator to evaluate the profile measurement accuracy of the large-scale stepped shaft, and compares our model with the dual-systematic errors model and the five-systematic errors model. The experimental results show that compared with the other two methods, the coaxiality measurement accuracy of standard stepped shaft No. 1 can be increased by 26.03% and 15.99%, respectively; the cylindricity measurement accuracy of standard stepped shaft No. 1 can be increased by 16.03% and 9.17%, respectively; the coaxiality measurement accuracy of the No. 2 standard stepped shaft can be increased by 29.86% and 16.29%, respectively; the cylindricity measurement accuracy of standard stepped shaft No. 2 can be increased by 17.32% and 10.46%, respectively –– this verifies the effectiveness of our measurement method. The measurement method used in this study provides an accurate theoretical basis for the implementation of high-precision model engineering of cylindrical parts for national metrology institutions and key laboratories.